Structure, function and evolution of the animal mitochondrial replicative DNA helicase - Kaguni, Laurie S.; Oliveira, Marcos T. [UNESP] (Taylor & Francis Ltd, 2016)
The mitochondrial replicative DNA helicase is essential for animal mitochondrial DNA (mtDNA) maintenance. Deleterious mutations in the gene that encodes it cause mitochondrial dysfunction manifested in developmental delays, defects and arrest, limited life span, and a number of human pathogenic phenotypes that are recapitulated in animals across taxa. In fact, the replicative mtDNA helicase was discovered with the identification of human disease mutations in its nuclear gene, and based upon its deduced amino acid sequence homology with bacteriophage T7 gene 4 protein (T7 gp4), a bi-functional primase-helicase. Since that time, numerous investigations of its structure, mechanism, and physiological relevance have been reported, and human disease alleles have been modeled in the human, mouse, and Drosophila systems. Here, we review this literature and draw evolutionary comparisons that serve to shed light on its divergent features.
Keywords: Animal models; DNA helicase; DNA replication; enzymology; mitochondria